The effect of organic and mineral fertilizers on the fruit yield Cucurbita pepo L. - Almudhafar , Inaam M.; Obaid, Mohammed H. (Journal of Kerbala for Agricultural Sciences, 2024)
The experiment was carried out in the vegetable field of the Department of Horticulture and Landscape Engineering, College of Agriculture, University of Karbala - Al-Husseiniyah District during the fall semester 2023-2024 in sandy soil according to a randomized completely block design (RCBD). The experiment included 19 treatments and three repetitions. Vermicompost tea was added to the soil at three levels (4, 8 and 12) liter ha-1, and humic extract was added at three levels as well (6, 12 and 18) liter ha-1. It was added to the soil in three batches, and three levels of NPK mineral fertilizer (25%, 50%, and75%) of the fertilizer recommendation with compared to a treatment to which the full fertilizer recommendation(100%) NPK)Comparison (,was applied in three stages to investigate the impact of vermicompost tea humic acid and mineral fertilizer (NPK) on the quality of zucchini squash The results showed a significant effect of the highest concentration of vermicompost tea and mineral fertilizer 75% on the characteristics of fruit length and fruit weight, as treatment F12 excelled by giving it the highest rate of the mentioned characteristics, amounting to 18.90 cm and 210.90 g fruit -1, and treatment F10 recorded the highest rate of fruit number characteristic of 5.63 fruit-1. The results also showed that the F3 treatment was superior in terms of fruit diameter, reaching 4.132 cm. We conclude from this that it is preferable to divide the organic and mineral fertilizers into batches, and it is possible to use quality organic fertilizer with a third of the amount of mineral fertilizer, that is, reducing mineral fertilizers and replacing them with organic fertilizers.